Dietary Patterns and Alcohol Consumption During Pregnancy: Secondary Analysis of Avon Longitudinal Study of Parents and Children. (19th April 2017) - Coathup, Victoria; Northstone, Kate; Gray, Ron; Wheeler, Simon; Smith, Lesley
Abstract : Background: Large general population surveys show that heavy regular and episodic alcohol consumption are associated with lower intakes of fruits and vegetables, and higher intakes of processed and fried meat. This is of particular concern regarding pregnant women, as both alcohol intake and inadequate maternal nutrition are independently associated with adverse fetal outcomes. The current study aimed to determine associations between maternal dietary patterns and alcohol consumption during pregnancy. Methods: Women were participating in the Avon Longitudinal Study of Parents and Children, and provided details of alcohol consumption at 18 weeks' gestation and diet at 32 weeks' gestation ( n  = 9, 839). Dietary patterns were derived from the food frequency questionnaire data using principal components analysis. Associations between alcohol consumption and dietary patterns were determined using multiple linear regression, adjusted for various sociodemographic and lifestyle factors. Results: After adjustment, drinking ≥1 unit/d during the first trimester ( β  = 0.23 [95% CI: 0.08, 0.38]; p  = 0.002) and binge drinking (≥4 units in 1 day) during the first half of pregnancy ( β  = 0.14 [95% CI: 0.07, 0.21]; p  < 0.0001) were associated with greater adherence to the "Processed" dietary pattern (high intakes of processed meat and low intakes of fruit and vegetables). Light‐to‐moderate alcohol consumption (≤1 drink/d) during the first trimester was associated with greater adherence to the "Health conscious" dietary pattern (high intakes of fruit, vegetables, whole grains, and fish) ( β  = 0.09 [95% CI: 0.04, 0.14]; p  < 0.0001). Conclusions: Two important components of health behavior during pregnancy appear to be related: greater consumption of processed foods associated with heavier alcohol consumption, and healthier dietary choices associated with light‐to‐moderate alcohol intake. Potential synergistic effects of these behaviors may have implications for maternal and fetal health and warrant further investigation. A more holistic approach to addressing health behaviors in women of reproductive age is required. Abstract : Alcohol intake and inadequate maternal nutrition during pregnancy are independently associated with adverse fetal outcomes. We conducted a secondary analysis of data from a UK birth cohort and explored associations between maternal dietary patterns and alcohol consumption during pregnancy. Two important components of health behaviour during pregnancy appear to be related; greater consumption of processed foods associated with heavier alcohol consumption, and healthier dietary choices associated with light to moderate alcohol intake. These relationships may have implications for fetal health.